ChemInform Abstract: Recent Advances in Catalytic CO2 Reduction by Organometal Complexes Anchored on Modified Electrodes. Issue 37 (August 2016) - Sun, Cunfa; Gobetto, Roberto; Nervi, Carlo
Abstract: Review: 45 refs.